2019
DOI: 10.1016/j.abb.2019.108111
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the conserved reentrant membrane helix in the monotopic phosphoglycosyl transferase superfamily supports key molecular interactions with polyprenol phosphate substrates

Abstract: Investigation of the conserved reentrant membrane helix in the monotopic phosphoglycosyl transferase superfamily supports key molecular interactions with polyprenol phosphate substrates The MIT Faculty has made this article openly available. Please share how this access benefits you. Your story matters. Citation Entova, Sonya et al. "Investigation of the conserved reentrant membrane helix in the monotopic phosphoglycosyl transferase superfamily supports key molecular interactions with polyprenol phosphate subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 68 publications
2
15
0
Order By: Relevance
“…11,12,25,30 It has also recently been suggested that the unique geometry of BP may aid in binding to PGTs and may also facilitate interactions at the membrane interface. 31 It is possible that lipophilic polyisoprenoids, when added with surfactants or organic alcohols, do not necessarily share these same properties as an artifact of exogenous supplementation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…11,12,25,30 It has also recently been suggested that the unique geometry of BP may aid in binding to PGTs and may also facilitate interactions at the membrane interface. 31 It is possible that lipophilic polyisoprenoids, when added with surfactants or organic alcohols, do not necessarily share these same properties as an artifact of exogenous supplementation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The prevalence of sugar-modifying and GT bifunctional enzymes is consistent with the existence of protein-protein interactions facilitating product transfers within the respective pathways. Fusions with regulatory domains point to possible regulation of glycan biosynthesis at the PGT reaction specifically, allowing for conservative use of the limited supply of PrenP (48), the common substrate in these glycoconjugate biosynthesis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, it is possible that these polyPGT F -monoPGT NF fusion enzymes resemble an ancestral enzyme. Notably, the monoPGT-core fold, exemplified by C. jejuni PglC, has been shown to increase the local membrane concentration of the PrenP substrate (48). Such an enrichment could increase catalytic throughput of the fused polyPGT enzyme and confer a selective advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoglycosyl transferase PglC from Campylobacter consicus is an example of the other family, dual domain phosphoglycosyl transferases. Mechanistic studies on the enzyme have shown that the reaction is a two-step process with a covalent intermediate [112,113]. A nucleophilic side chain attacks on the phosphate, forming an intermediate that is attacked by the prenyl phosphate in the second step.…”
Section: Catalysis Phosphoglycosyl Transferasesmentioning
confidence: 99%
“…An aspartate in a conserved Asp-Glu dyad has been proposed as the attacking nucleophile, while the glutamic acid residue has been speculated to assist the release of UMP and nucleophilic attack by Pren-P. Phosphoglycosyl transferase PglC from Campylobacter consicus is an example of the other family, dual domain phosphoglycosyl transferases. Mechanistic studies on the enzyme have shown that the reaction is a two-step process with a covalent intermediate [112,113]. A nucleophilic side chain attacks on the phosphate, forming an intermediate that is attacked by the prenyl phosphate in the second step.…”
Section: Catalysis Phosphoglycosyl Transferasesmentioning
confidence: 99%